Lactic Acid Bacteria for Delivery of Endogenous or Engineered Therapeutic Molecules - Bron, Peter A.; Kleerebezem, Michiel (Frontiers in Microbiology, 2018)
Food-grade lactic acid bacteria (LAB) are considered suitable vehicles for the production and/or delivery of health promoting or therapeutic, bioactive molecules. The molecules considered for health-beneficial use include the endogenous effector molecules produced by probiotics (mostly lactobacilli), as well as heterologous bioactives that can be produced in LAB by genetic engineering (mostly using lactococci). Both strategies aim to deliver appropriate dosages of specific bioactive molecules to the site of action. This review uses specific examples of both strategies to illustrate the different avenues of research involved in these applications as well as their translation to human health-promoting applications. These examples pinpoint that despite the promising perspectives of these approaches, the evidence for their effective applications in human populations is lagging behind.